STATUS GIZI ANAK SEKOLAH DI MI DARUSSALAM KOTA BENGKULU - irfina syafitri; Bintang Agustina Pratiwi (JURNAL MEDIA KESEHATAN, 2023)
Problem: Children are one of Indonesia's future human resource assets that should receive more attention, especially those who are experiencing a period of growth and development, so they need adequate food consumption with balanced nutrition because strong, healthy, and intelligent children are a determinant of the nation's sustainability. Nutritional status is a measure of success in fulfilling nutrition for children. Research Objectives: This study aims to determine the nutritional status of school children at MI Darussalam, Bengkulu City. Research Methods: This study used a descriptive survey with a cross-sectional design. The population of this study was 131 students, with a total sample of 57 respondents. Then, the collection of data on nutritional status was carried out by weighing the weight using a stamping scale and measuring the height using a microtoise. Results: Assessment of children's nutritional status was carried out by calculating BMI (weight/height), and the results obtained were 43 respondents (75.4%) with good nutritional status, 5 (five) respondents (8.7%) with poor nutritional status, 7 (seven) respondents (12.2%) ) with more nutritional status and 2 (two) respondents (3.5%) with obesity. Conclusion: Malnutrition, overnutrition, and obesity are still found in children at MI Darussalam, Bengkulu City.